2017
DOI: 10.1111/pce.12994
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of LESION SIMULATING DISEASE 1 as a condition‐dependent scaffold protein and transcription regulator

Abstract: Since its discovery over two decades ago as an important cell death regulator in Arabidopsis thaliana, the role of LESION SIMULATING DISEASE 1 (LSD1) has been studied intensively within both biotic and abiotic stress responses as well as with respect to plant fitness regulation. However, its molecular mode of action remains enigmatic. Here, we demonstrate that nucleo-cytoplasmic LSD1 interacts with a broad range of other proteins that are engaged in various molecular pathways such as ubiquitination, methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 104 publications
(190 reference statements)
2
48
0
Order By: Relevance
“…However, there could be also another scenario and plant strategy to communicate different stimuli and induce the systemic responses to local stress. In some cases, a cross-talk is seen, in which one type of locally applied stress is capable of generating a protective response or acclimation to another type of biotic or abiotic stress (Mühlenbock et al, 2008 ; Szechyńska-Hebda et al, 2015 , 2016a , b ; Czarnocka et al, 2017 ). The environmental factors, like a sudden increase in light intensity, changes in temperature, limitation in water accessibility, or pathogen attack, all of them depress efficiency of CO 2 assimilation due to reduction of stomatal conductance, but do not limit foliar absorption of light energy (Müller et al, 2001 ; Mullineaux and Karpiński, 2002 ; Holt et al, 2004 ; Baker, 2008 ).…”
Section: Systemic Propagation Of Electrical Signals In Plantsmentioning
confidence: 99%
“…However, there could be also another scenario and plant strategy to communicate different stimuli and induce the systemic responses to local stress. In some cases, a cross-talk is seen, in which one type of locally applied stress is capable of generating a protective response or acclimation to another type of biotic or abiotic stress (Mühlenbock et al, 2008 ; Szechyńska-Hebda et al, 2015 , 2016a , b ; Czarnocka et al, 2017 ). The environmental factors, like a sudden increase in light intensity, changes in temperature, limitation in water accessibility, or pathogen attack, all of them depress efficiency of CO 2 assimilation due to reduction of stomatal conductance, but do not limit foliar absorption of light energy (Müller et al, 2001 ; Mullineaux and Karpiński, 2002 ; Holt et al, 2004 ; Baker, 2008 ).…”
Section: Systemic Propagation Of Electrical Signals In Plantsmentioning
confidence: 99%
“…Moreover, LSD1, EDS1 and PAD4 regulate photosynthesis, water use efficiency (WUE) and seed yield in a condition‐dependent manner, thereby differentiating plant responses in field and laboratory conditions (Wituszyńska et al ). Furthermore, LSD1 is a condition‐dependent scaffold protein and transcription regulator, and forms dimers with EDS1 (Czarnocka et al ). Recently, we reported that PAD4 and EDS1 can function in woody plants in a similar manner as in Arabidopsis (Ślesak et al , Szechyńska‐Hebda et al , Bernacki et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of FMO1 was shown to be elevated in lsd1 background previously and confirmed in the current study ( Supplementary Figure S1 ), which strengthens the demonstrated contribution of FMO1 to the LSD1-dependent cell death pathway ( Figure 5 ). LSD1 has been recently demonstrated as a transcriptional regulator [ 47 ]. Although the FMO1 promoter was not among LSD1-bound sequences [ 47 ], it is possible that LSD1 inhibits FMO1 expression in an indirect manner, through another transcription regulator.…”
Section: Discussionmentioning
confidence: 99%
“…LSD1 has been recently demonstrated as a transcriptional regulator [ 47 ]. Although the FMO1 promoter was not among LSD1-bound sequences [ 47 ], it is possible that LSD1 inhibits FMO1 expression in an indirect manner, through another transcription regulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation